Implemented actions by the Anticorruption System of the State of Sonora in the context of sanitary emergency caused by COVID-19 - Palafox Duarte, María Inés (Posgrados de la División de Ciencias Económica Administrativas, 2021)
This research aims to analyze the anti-corruption actions undertaken by the government of the State of Sonora through the institutions that make up the State Anti-Corruption System, based on the declaration of a COVID-19 pandemic. The foregoing applied to sectors of the public administration that are exposed to improper practices during the pandemic, thereby contributing to reducing the risk of corruption or, in any case, quickly identifying it and being informed to the authority competent. The above was developed using the informative documentary method, since reliable sources on the subject were used, contributing to analyze and select the relevant information on the subject under study.